2016
DOI: 10.1016/j.jfca.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Mineral micronutrient and prebiotic carbohydrate profiles of USA-grown kale (Brassica oleracea L. var. acephala)

Abstract: Kale (Brassica oleracea L. var. acephala.) is a leafy green brassica vegetable, the production levels of which have increased over the past 10 years due to increased demand by North American consumers. Kale is perceived to be highly nutritious leafy green vegetable even though

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
49
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 21 publications
7
49
0
6
Order By: Relevance
“…Turnip sample displayed a higher concentration of oligosaccharides than monosaccharides (about double times). This behavior was in accordance with the literature data from Brassica oleracea leaves [54]. Different studies described that mannose is present in the structure of the functional protein as ligands or signaling molecules [55,56].…”
Section: Proximate Chemical Profilesupporting
confidence: 92%
“…Turnip sample displayed a higher concentration of oligosaccharides than monosaccharides (about double times). This behavior was in accordance with the literature data from Brassica oleracea leaves [54]. Different studies described that mannose is present in the structure of the functional protein as ligands or signaling molecules [55,56].…”
Section: Proximate Chemical Profilesupporting
confidence: 92%
“…Thavarajah et al. (2016) obtained similar results for fresh kale samples—the average content of K, Ca, and Mn in the examined kale grown in the United States was 488, 106, and 0.8 mg/100 g, respectively. Moreover, the present study indicated a slightly higher content of Mg and lower content of Fe and Zn compared to kale grown in the United States (Mg = 44 mg/100 g, Fe = 1.1 mg/100 g, and Zn = 0.7 mg/100 g).…”
Section: Resultsmentioning
confidence: 56%
“…Previous studies have shown that kale is a rich source of minerals, such as Ca, Mg, K, Na, Fe, and Cu (Jahangir, Kim, Choi, & Verpoorte, 2009; Thavarajah et al., 2016). In our study, there were no significant differences in mineral content at different fermentation stages (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diferentemente da couve-manteiga, suas folhas são crespas, onduladas e, geralmente, de coloração verde-escura (Olsen et al, 2009;Pathirana et al, 2017). Ambas as couves são fontes de sais minerais, fibras e proteína, contudo kale supera a couve-manteiga em 31, 16 e 48%, respectivamente (Universidade Estadual de Campinas, 2006;Thavarajah et al, 2016;United States Department of Agriculture, 2016).…”
unclassified